READING ON THE PHENOMENON OF ISLAMIC EDUCATION THROUGH NYADRAN TRADITION IN BANYUMAS DISTRICT - Wiji Nurasih; Muhamad Yusuf; Rifqi Nurdiansyah; Doli Witro (UIN Sumatera Utara Medan, 2022)
This article aims to describe the interconnection integration of Quranic Tafsir and Anthropology as an analysis of the value of Islamic education in the Nyadran tradition that developed in Semedo Village, Pekuncen District, Banyumas Regency. Nyadran by the Javanese is carried out to welcome the month of Ramadan. At first, Nyadran was a ritual of worship of ancestral spirits carried out by Hindu-Buddhist. However, as Islam came to the archipelago, this tradition was transformed so that it became a tradition containing local wisdom that synergized with Islamic values. This article uses a qualitative method of field research. Data was obtained by conducting observations, interviews and literature review. Data analysis techniques are condensation, data presentation, and concluding. This study found that the Nyadran tradition conveys many values and messages of Islamic education following the Quran and hadith in its implementation. The educational values are the values of aqidah, shari'ah values and moral values. While the messages conveyed through the Nyadran tradition include invitations to maintain cleanliness, remember death, and be devoted to parents and others.